Analisis Kebutuhan Peralatan Penunjang Pelayanan Persampahan di Distrik Mimika Baru, Kabupaten Mimika - Alfons, Alfred Benjamin; Sarah Jessie Aprina Ubruangge (Jurnal Serambi Engineering, 2025)
Mimika Baru District in Mimika Regency is experiencing rapid population growth and economic activity, this also has an impact on the increase of municipal solid waste generated by the area. This study aims to predict the volume of municipal solid waste generated by the community in Mimika Baru District which is then used as the basis for calculating the needs for supporting equipment of solid waste services to support waste services for the community in Mimika Baru District. The analysis of municipal solid waste generation and the needs for supporting equipment of solid waste services refers to SNI 19-3964-1994 and SNI 3242-2008. The results of the analysis show that the volume of municipal solid waste generation in Mimika Baru District will increase from 803,071.08 liters/day in 2024, projected to 809,495.65 liters/day in 2025, then increase again to 876,637.09 liters/day in 2035 and then 949,347.39 liters/day in 2045. The number of assistance equipment in 2045. waste such as temporary waste shelters needed will increase from 15 units in 2025 to 20 units in 2045. The waste transportation fleet also needs to be increased, such as garbage trucks which previously numbered 16 units in 2025 increased to 20 units in 2045, while gerbage motorbikes waste which previously increased by 23 units in 2025 increased to 79 units in 2045.